16. CURRENT KNOWLEDGE AND PRACTICES OF THE RAGLAI ETHNIC GROUP IN BAC AI DISTRICT, NINH THUAN PROVINCE, REGARDING CHILD MARRIAGE AND CONSANGUINEOUS MARRIAGE LEGISLATION (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current knowledge and practices of the Raglai ethnic group in Bac Ai District, Ninh Thuan Province, concerning child marriage and consanguineous marriage legislation.Subjects and Methods: A cross-sectional descriptive study was conducted, sampling 400 Raglai people residing in Bac Ai District, Ninh Thuan Province. Knowledge and practices were assessed through interviews using a pre-prepared questionnaire.Results: The overall correct knowledge and practices regarding child marriage and consanguineous marriage legislation were 67.3%. There was a correlation between general knowledge and practices on child marriage and consanguineous marriage with demographic factors, including education level, place of residence, occupation of the participants, mother's education level, mother's occupation, father's education level, father's occupation, number of siblings, and economic status.Conclusion: Knowledge of the legislation on child marriage and consanguineous marriage remains limited. Strengthening communication activities to prevent child marriage is essential and serves as an effective solution in improving the health of the Raglai ethnic community.
Keywords: knowledge; child marriage; Raglai